2021
DOI: 10.4018/ijseims.2021070106
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Type I Collagen - A Review on Artificial Alignment Strategies

Abstract: Collagen is the most abundant protein in the human body and serves many functions, from mechanical stability and elasticity in tendons and bone, to optical properties, such as transparency and a fine tuned refractive index in the cornea of the eye. Collagen has interested humankind for centuries: Leonardo Da Vinci studied and drew the tendons in the human body precisely in the 15th and 16th century. A look at the literature reveals easily > 200,000 papers. This article reviews oriented type I collagen artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Interestingly, it was confirmed that the mechanism of alignment was a combination of both flow (due to bead movement) and the magnetic field. When either variable is removed, the scaffolds did not align [ 11 , 86 ]. When crosslinked with genipin (0.25%), the scaffolds possessed a tangent modulus of approximately 1 MPa and a strain of 0.035%, higher than that of conventional collagen gels [ 87 ].…”
Section: Overview Of Collagen Alignment Techniquesmentioning
confidence: 99%
“…Interestingly, it was confirmed that the mechanism of alignment was a combination of both flow (due to bead movement) and the magnetic field. When either variable is removed, the scaffolds did not align [ 11 , 86 ]. When crosslinked with genipin (0.25%), the scaffolds possessed a tangent modulus of approximately 1 MPa and a strain of 0.035%, higher than that of conventional collagen gels [ 87 ].…”
Section: Overview Of Collagen Alignment Techniquesmentioning
confidence: 99%